PENINGKATAN HASIL BELAJAR PENDIDIKAN PANCASILA MENGGUNAKAN MODEL EXAMPLE NON EXAMPLE DI KELAS IV SDN 08 ALANG LAWAS - Panggabean, Lila; Atri Waldi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to explain the improvement of learning outcomes through the model Example Non Example on learning Pancasila Education Materials Norms and Rules in Class IV SDN 08 Alang Lawas Kota Padang. This Class Action Research (PTK) uses a qualitative and quantitative approach with the subjects of teachers and 20 students of SDN 08 Alang Lawas. The research is conducted in two cycles, with a research procedure consisting of planning, implementation, observation, and reflection. Test and non-test data collection techniques. The results of the study show that: first, cycle I learning module obtained an average of 85.4% (B) increased in cycle II to 95.8% (SB). Secondly, the I-cycle teacher aspect gained an average of 81.25% (B), increasing in the II cycle to 96.87%, (SB). Third, the aspect of cycle I pupils obtained an average of 79.65% (C), increasing in cycle II to 97.75% (SB). Fourthly, the learning outcome of cycle I pupils averaged 72.6(C), increasing in cycle II to 88 (B). Thus, the Model Example No Example is able to improve the learning outcomes of pupils in learning Pancasila Education in Class IV SDN 08 Alang Lawas Kota Padang.